A review of loop heat pipes for aircraft anti-icing applications. (5th February 2018) - Su, Qian; Chang, Shinan; Zhao, Yuanyuan; Zheng, Haikun; Dang, Chaobin
Highlights: The application environment of the loop heat pipe ice protection system (LHPIPS) is described. The fundamental design of the LHPIPS is introduced. A series of optimization strategies regarding the LHPIPSs are proposed to enhance their operating performance. The feasibility and practicability of utilizing the LHPIPS for aircraft anti-icing have been proved. Abstract: Loop heat pipes (LHPs) are highly efficient two-phase heat transfer devices with the ability to transport significant amounts of heat over long distances. Owing to the increasing demand of anti-icing applications in aircraft, certain investigations regarding LHP anti-icing have been successfully conducted, which verified the anti-icing capacity and feasibility of loop heat pipe ice protection system (LHPIPS). In this work, we will conduct a deep analysis on the LHP application to aircraft anti-icing. After a brief introduction of the historical application background and application environment of the LHPIPS, a detailed description of its fundamental design will be elucidated, followed by a series of optimization strategies, including the graphene-coating integration technology, the adoption of bidisperse wicks, the introduction of nanofluids, and the use of double compensation chamber loop heat pipe (DCCLHP). We present the additional points that require further study and that could be further optimized for the development of the LHPIPS. This work contributes to a thorough understanding of the novel and promising LHPIPS, as well as guides its future designs and applications.